(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
2020 was a different year, complicated and of constant uncertainty. This has also affected the child population. Therefore, the aim of the study was to determine the relationship between daily stress and emotional intelligence of elementary school students. The type of study used was descriptive correlational and the design was non-experimental - transversal. The sample consisted of 166 students of both sexes, from 3rd, 4th, 5th and 6th grade of elementary school in a public school, for which a non-probabilistic sampling was used. The instruments used for data collection were: the Daily Stress Inventory for the first variable and the Bar ON ICE - NA Emotional Intelligence Inventory for the second variable. The results indicated that there is a negative relationship of 0.412 (rs = 0.412, p < 0.05) between both variables, validating the proposed hypothesis. It was concluded that daily stress is inversely related to the development of emotional intelligence, and that the dimensions of emotional intelligence should be worked on to reduce stress levels.